COMBINED AUTOLOGOUS TRANSPLANTATION OF NEUROSENSORY RETINA, RETINAL PIGMENT EPITHELIUM, AND CHOROID FREE GRAFTS. (September 2018) - Parolini, Barbara; Grewal, Dilraj S.; Pinackatt, Sajish J.; Baldi, Andrea; Di Salvatore, Attilio; Besozzi, Gianluca; Finzi, Alessandro; Cardillo, Daniele; Mahmoud, Tamer H.
Abstract : Purpose: To evaluate the feasibility and initial functional and anatomical outcomes of transplanting a full-thickness free graft of choroid and retinal pigment epithelium (RPE), along with neurosensory retina in advanced fibrosis and atrophy associated with end-stage exudative age-related macular degeneration with and without a concurrent refractory macular hole. Methods: During vitrectomy, an RPE–choroidal and neurosensory retinal free graft was harvested in nine eyes of nine patients. The RPE–choroidal and neurosensory retinal free graft was either placed subretinally (n = 5), intraretinally to cover the foveal area inside an iatrogenically induced macular hole over the RPE–choroidal graft (n = 3) or preretinally (n = 1) without a retinotomy wherein both free grafts were placed over the concurrent macular hole. Silicone oil endotamponade was used in all cases. Results: Mean follow-up was 7 ± 5.5 months (range 3–19). The mean preoperative visual acuity was ∼count fingers (logarithm of the minimum angle of resolution = 2.11, range 2–3), which improved to ∼20/800 (logarithm of the minimum angle of resolution 1.62 ± 0.48, range 0.7–2, P = 0.04). Vision was stable in 5 eyes (55.6%) and improved in 4 eyes (44.4%). Reading ability improved in 5 eyes (55.6%). Postoperative complications were graft atrophy (n = 1), epiretinal membrane (n = 1), and dislocation of neurosensory retina–choroid–RPE free graft (n = 1). Conclusion: Combined autologous RPE–choroid and neurosensory retinal free graft is a potential surgical alternative in eyes with end-stage exudative age-related macular degeneration, including concurrent refractory macular hole. Abstract : Supplemental Digital Content is Available in the Text.The authors demonstrate the feasibility of transplanting a full-thickness autologous free graft of choroid and retinal pigment epithelium, along with neurosensory retina in eyes with advanced fibrosis and atrophy in end-stage exudative age-related macular degeneration including the presence of an associated refractory macular hole. Some degree of functional improvement was noted in 55.6% eyes.